2013
DOI: 10.1152/advan.00136.2012
|View full text |Cite
|
Sign up to set email alerts
|

Training TAs in scientific teaching for the human physiology and anatomy laboratory

Abstract: SCIENTIFIC TEACHING (ST) is a method developed nearly a decade ago by Handelsman and colleagues (2) in which instructional practice in undergraduate science is based on current educational research findings and established best practices. The ST approach uses a process in which all students, especially those in courses with large enrollments, are more actively engaged in learning compared with traditional lecture-based courses.Unique to ST is an active learning and inquiry-based framework that aims to ensure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This professor was trained in and used the practices of active-learning pedagogies (e.g., defining learning goals, formative assessment strategies) consistent with current developments in discipline-based educational research (DBER). The active-learning principles associated with scientific teaching encourage student engagement by, for example, calling upon students to think critically, participate in collaborative discussion, and consider ways they can best achieve learning objectives (Chen et al ., 2013). This instructor also self-reported a high level of scientific teaching pedagogy adoption on a census survey sent to all past Summer Institute participants from 2004 to 2014 (Aragón et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This professor was trained in and used the practices of active-learning pedagogies (e.g., defining learning goals, formative assessment strategies) consistent with current developments in discipline-based educational research (DBER). The active-learning principles associated with scientific teaching encourage student engagement by, for example, calling upon students to think critically, participate in collaborative discussion, and consider ways they can best achieve learning objectives (Chen et al ., 2013). This instructor also self-reported a high level of scientific teaching pedagogy adoption on a census survey sent to all past Summer Institute participants from 2004 to 2014 (Aragón et al ., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…There are only a few published examples of ST being explicitly integrated into PD for GTAs assigned to STEM courses. In a pilot study, Chen et al (2013) conducted an ST-based workshop for GTAs who were teaching a laboratory course in anatomy and physiology (A&P). Students in the A&P lab class reported higher learning gains than students in a similar A&P lab class in which GTAs had not received ST training, suggesting that ST training improved instructional practices.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, various studies have reported evidence for a relationship between participation in PD and GTA knowledge, self-efficacy, and/or anxiety ( Hardré, 2003 ; Harris et al ., 2009 ; DeChenne et al ., 2012 , 2015 ; Bauer et al ., 2013 ; Pelton, 2014 ). The relationship between PD and GTA instructional planning, delivery, and assessment (GTA teaching practice) has also been examined ( Baumgartner, 2007 ; Marbach-Ad et al , 2012 ; Chen et al , 2013 ; Wyse et al , 2014 ). In several posttest-only studies, GTAs reported that their instructional practices improved with the training; or that they implemented practices taught during the training ( Baumgartner, 2007 ; Hardré and Burris, 2012 ; Pentecost et al ., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The need for science, technology, engineering and math (STEM) majors is outpacing their production with a projected need for one million trained STEM professionals by this year (2018) according to a report by the President's Council of Advisors on Science and Technology (PCAST, 2012). Several longitudinal studies have found that students are interested in STEM majors but tend to switch to other majors primarily in the first two years of college in large part due to continued use of passive lecture techniques (Chen, 2013;Graham, et al, 2013;Lowell, et al, 2009;Mervis, 2010;Stains et al, 2018;. They are not challenged to analyze, apply or evaluate scenarios that can be applied to real life situations which leaves them without the skills needed to apply their knowledge (AAAS, 2011;Burrowes, 2003, DiCarlo, 2006Lujan andDiCarlo, 2005, NRC, 2003).…”
Section: Transforming Science Educationmentioning
confidence: 99%
“…While nearly 30% of students seeking bachelor's degrees initially choose STEM fields, almost half of these leave STEM before graduation (Chen, 2013). Many students who begin college as STEM majors find themselves leaving, often in the first two years, because the teaching methods are less than favorable (Chen, 2013;Graham, et al, 2013;Lowell, et al, 2009;Mervis, 2010;. Among other things, students encounter a focus on memorization and regurgitation of content that turns them off to the sciences.…”
Section: Introductionmentioning
confidence: 99%